2013
DOI: 10.1111/jvh.12108
|View full text |Cite
|
Sign up to set email alerts
|

Regression of liver fibrosis is progressive after sustained virological response to HCV therapy in patients with hepatitis C and HIV coinfection

Abstract: There are few data about the long-term histological outcome of HIV-/HCV-coinfected patients after therapy with interferon and ribavirin. We performed an observational study of 216 patients who received therapy against HCV and who had at least three successive transient elastographies (TE) during the follow-up. The primary endpoint was confirmed fibrosis regression, defined as a reduction of at least 1 point in Metavir fibrosis score, confirmed and without worsening in successive TE. At baseline, 23% had fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…This study aims at assessing the long-term impact of this regimen in terms of liver disease progression, immunological recovery and overall clinical improvement in a cohort of HIV-HCV co-infected patients after a median 8-year follow-up. First, as previously reported in both HCV mono-infected and HIV-HCV co-infected patients [19], our study confirms that the achievement of SVR is beneficial in terms of liver-related mortality and fibrosis regression. The effect of HCV clearance was evident when considering that six liver-related deaths were restricted to patients in the non-SVR group, while no liver-related clinically significant event was reported in the SVR-group.…”
Section: Discussionsupporting
confidence: 91%
“…This study aims at assessing the long-term impact of this regimen in terms of liver disease progression, immunological recovery and overall clinical improvement in a cohort of HIV-HCV co-infected patients after a median 8-year follow-up. First, as previously reported in both HCV mono-infected and HIV-HCV co-infected patients [19], our study confirms that the achievement of SVR is beneficial in terms of liver-related mortality and fibrosis regression. The effect of HCV clearance was evident when considering that six liver-related deaths were restricted to patients in the non-SVR group, while no liver-related clinically significant event was reported in the SVR-group.…”
Section: Discussionsupporting
confidence: 91%
“…Significant histologic improvements have been documented in studies of paired liver biopsies from patients with chronic hepatitis C who achieved sustained viral eradication (Poynard et al 2002;Shiratori et al 2000) and patients with chronic hepatitis B who received long-term antiviral therapy (Chang et al 2010;Hadziyannis et al 2006). Several studies reported a significant decrease in liver stiffness values, compared with baseline values, in patients with HCV who achieved sustained viral eradication (Fontana et al 2009;Hezode et al 2011;Martinez et al 2011b;Ogawa et al 2009;Vergniol et al 2009;Stasi et al 2013;Casado et al 2013), as well as in HBV-infected patients treated with nucleoside analog drugs (Enomoto et al 2010;Fung et al 2011b;Lim et al 2011;Ogawa et al 2011;Osakabe et al 2011;Wong et al 2011;Kim et al 2013;Kuo et al 2014).…”
mentioning
confidence: 90%
“…We, and others, have found an important rate of fibrosis regression (FR) during the follow-up in HIV-/HCV-coinfected patients obtaining SVR [7,14,15]. In hypothesis, FR after SVR should be associated with even a lower risk of hepatic complications, and a prolonged survival.…”
Section: Introductionmentioning
confidence: 93%